A timely question: How can we not talk about becoming a professor in the context of a neoliberal and decolonising higher education? - Mgqwashu, Emmanuel Mfanafuthi (Critical Studies in Teaching and Learning, 2024)
Drawing from my own experiences and critical reflections on my journey to becoming a professor, I show how two types of pressures facing higher education institutions necessitate a revisiting of the role of a professor. These pressures are, firstly, to account for “market-friendliness” and, secondly, to respond to the transformation and decolonisation imperatives as a result of massification. I show the broader socio-economic and political conditions under which universities exist and the impact these have on the knowledge project. I argue that such impact manifests through instrumental reasoning and the commodification of knowledge, as well as “Western hegemony” over others. I then explore the extent to which a professorial role may need to re-adapt in order to respond to these broader socio-economic and political exigencies that continue to spill over into higher education.